Hydrogel platform capable of molecularly resolved pulling on cells for mechanotransduction. (15th December 2022) - Cheng, Nan; Zhang, Yile; Wu, Yukai; Li, Bohan; Wang, Hong; Chen, Shaojie; Zhao, Peng; Cui, Jiaxi; Shen, Xiaoqin; Zhu, Xingjun; Zheng, Yijun
Abstract: The active forces exerted from the extracellular matrix (ECM) to mechanoreceptors have crucial impact on many cell functions and disease development. However, our understanding of the underlying mechanisms is held back due to the lack of ECM mimicking platform able to apply molecularly resolved forces to cells. Herein, we present novel hydrogel platform capable of generate pN range forces to specific cellular receptors, at molecular scale. This capability was achieved through near-infrared (NIR) light regulated macromolecular actuators functionalized within the platform. This platform enables us to reveal cell responses to molecularly resolved forces under controlled magnitude (150–400 ​pN) and frequency (up to 100 ​Hz) on matrix with varied stiffness. We find the stiffness of the matrix has a large influence on the applied force transduction to cells. This versatile platform holds the potential for establishing correlation between receptor signaling pathways and cellular responses closer to physiological conditions. Graphical abstract: Image 1